2021
DOI: 10.26699/jnk.v8i1.art.p071-077
|View full text |Cite
|
Sign up to set email alerts
|

Development Analysis of Post Graduate School Program of Occupational Health Nursing (OHN), Workforce and The Challenges in Poltekkes Kemenkes Jayapura (a Case Study)

Abstract: Background: According to the Central Statistics Agency (BPS, 2020), Papua is one of the poorest provinces in Indonesia with a poverty rate of 26.8%. This condition is exacerbated by the lack of educational facilities including occupational health nursing (OHN) at the postgraduate level. Even though there are several large industries in Papua that are engaged in oil exploration to wood processing. As a result, there is an imbalance between the need for OHN nursing experts and the production of nurses due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…In Papua, there are 9 health campuses with various health departments spread over 29 districts (Tukayo et al, 2021). Five of the 29 districts are endemic areas (Sroyer et al, 2022).…”
Section: Study Limitationmentioning
confidence: 99%
“…In Papua, there are 9 health campuses with various health departments spread over 29 districts (Tukayo et al, 2021). Five of the 29 districts are endemic areas (Sroyer et al, 2022).…”
Section: Study Limitationmentioning
confidence: 99%
“…Stunting is the fourth most on the health program agenda in Indonesia in the world and is one of the priority health problems (Dewanti et al, 2019). More than 400 vocational midwifery educational institutions are spread across 37 provinces throughout Indonesia (Tukayo et al, 2021). Many studies have revealed the role of midwives in various activities in the community, whether directly related to stunting or not (Sumiaty et al, 2021;Wulandari & Kusumastuti, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The averages of nursing graduates in Indonesia are around 40.000 people per year (I. Tukayo et al, 2021). In terms of foreign language teaching, the course weight is between 2 and 4 semester credit units (SKS).…”
Section: Introductionmentioning
confidence: 99%